Analisis Kesulitan Siswa SMA dalam Memahami Materi Barisan dan Deret - Suci Hartati (SUPERMAT : Jurnal Pendidikan Matematika, 2021)
This study aims to find out: (1) errors made by students in solving problems related to sequences and series, (2) finding the cause of students making these mistakes through analysis of errors made, (3) finding solutions to solve the problem.The method used in this research is descriptive qualitative method. The instrument used in this research is a test instrument. The object of the research is 10 students of class X MIPA SMAN 1 Tarumajaya, Bekasi. The data were analyzed using data reduction, data presentation, and drawing conclusions. In reducing the data, the researcher classified and summarized the data based on the student’s abilities which were obtained from the analyzed test results. Based on the research that has been done, it was found that the student’s difficulties were as follows: (1) Students had difficulty in understanding the concepts of geometric and arithmetic sequences and series,(2) Students have difficulty in the counting process, it can be seen that there are student errors in calculating exponential multiplication, (3) students still have difficulty in distinguishing arithmetic and geometric sequences.